Structural modifications in Bermuda grass [Cynodon dactylon (L.) Pers.] ecotypes for adaptation to environmental heterogeneity - Tufail, Aasma; Ahmad, Farooq; Hameed, Mansoor; Ahsan, Muhammad; Okla, Mohammad K.; Siddiqua, Umme Habibah; Khalid, Noreen; Rashid, Madiha; Shah, Anis Ali; Hegab, Momtaz M.; AbdElgawad, Hamada (Frontiers in Plant Science, 2023)
Differently adapted ecotypes of Bermuda grass [Cynodon dactylon (L.) Pers.] were collected from various regions of the Punjab, Pakistan to evaluate differential structural and functional modifications that are specific to cope with environmental hazards. Each ecotype showed different type of modifications for their existence in a specific habitat that reflects to their ecological success. Derawar Fort-Saline desert showed anatomical modifications like stem cross-sectional area and leaf sheath thickness that contribute towards water storage, vascular tissues for proficient translocation of solutes and trichomes that provide resistance to water loss, hence water conservation is the first priority. Sclerification in root is the only notable modification in the G-SSA ecotype from saline arid habitat where rainfall is not as low as in the Cholistan Desert. Two ecotypes from hyper-saline wetlands, UL-HS and KL-HS relied upon the number and size of vascular tissue, central cavity and sclerification in stem that is important for conduction of solutes, water loss and bulk movement of salts, respectively. The ecotype from reclaimed site was not much different from its counterpart from hyper-saline dryland, and this might due to too short time to be required for the evolution of any specific characteristic. The ecotypes from non-saline habitats, M-RB and BG-NS showed no visible sclerification in their above or below ground plant parts and no other prominent modification. Anatomical characteristics represent adaptive components in C. dactylon ecotypes that ensure growth, survival and ecological success against environmental hazards, mainly by modifications for water conservation.